Digitally Induced Altered States as Facilitators of the Future Augmented Human Sensorium: Analysis of Science Fiction Representations - Belousov, Anatolii; Bujić, Mila; Macey, Joseph; Hamari, Juho (United States, 2026)
This work analyses science fiction narratives for the intersections between the evolution of sensory augmentation technologies and altered states of consciousness as means of adaptation to this evolution. It identifies four types of sensorium manipulation, namely replacement, expansion, sharing and suppression, with each relating to unique cognitive shifts. Their representations in science fiction suggest that at least three of them can benefit from the facilitation of these shifts through appropriate types of digitally induced altered states of consciousness.
UbiComp Companion '25: Companion of the 2025 ACM International Joint Conference on Pervasive and Ubiquitous Computing